Effects of protein–carbohydrate supplementation on immunity and resistance training outcomes: a double-blind, randomized, controlled clinical trial - Naclerio, Fernando (Eur J Appl Physiol, 2016)
PURPOSE: To examine the impact of ingesting hydrolyzed beef protein, whey protein, and carbohydrate on resistance training outcomes, body composition, muscle thickness, blood indices of health and salivary human neutrophil peptides (HNP1-3), as reference of humoral immunity followed an 8-week resistance training program in college athletes. METHODS: Twenty-seven recreationally physically active males and females (n = 9 per treatment) were randomly assigned to one of the three groups: hydrolyzed beef protein, whey protein, or non-protein isoenergetic carbohydrate. Treatment consisted of ingesting 20 g of supplement, mixed with orange juice, once a day immediately post-workout or before breakfast on non-training days. Measurements were performed pre- and post-intervention on total load (kg) lifted at the first and last workout, body composition (via plethysmography) vastus medialis thickness (mm) (via ultrasonography), and blood indices of health. Salivary HNP1-3 were determined before and after performing the first and last workout. RESULTS: Salivary concentration and secretion rates of the HNP1-3 decreased in the beef condition only from pre-first-workout (1.90 ± 0.83 μg/mL; 2.95 ± 2.83 μg/min, respectively) to pre-last-workout (0.92 ± 0.63 μg/mL, p = 0.025, d = 1.03; 0.76 ± 0.74 μg/min, p = 0.049, d = 0.95), and post-last-workout (0.95 ± 0.60 μg/mL, p = 0.032, d = 1.00; 0.59 ± 0.52 μg/min, p = 0.027, d = 1.02). No other significant differences between groups were observed. CONCLUSIONS: Supplementation with a carbohydrate–protein beverage may support resistance training outcomes in a comparable way as the ingestion of only carbohydrate. Furthermore, the ingestion of 20 g of hydrolyzed beef protein resulted in a decreased level and secretion rates of the HNP1-3 from baseline with no negative effect on blood indices of health. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00421-016-3520-x) contains supplementary material, which is available to authorized users.